A Schema of Islamic Legal Methodology (Usul Al-Fiqh) in Early Islam - Kazemi Moussavi, Ahmad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Schema of Islamic Legal Methodology (Usul Al-Fiqh) in Early Islam